A simple design for a helium scattering apparatus - Maier, Florian; Kneitz, Stefan; Koschel, Herbert; Steinrück, Hans-Peter (Surface Science, 1997)
We have designed a simple helium scattering apparatus for gas-surface scattering experiments. The effusive source is a glass multicapillary array, operated at large Knudsen numbers which produces a highly collimated thermal He beam (FWHM≈3°) with a Maxwellian velocity distribution. The detector is a Bayard Alpert ionization gauge, mounted in a tube that is separated from the main UHV chamber via a second multicapillary array. This setup allows one to select only those He atoms that are reflected by the sample in the specular direction and thus to measure the reflectivity of the surface. Examples of its performance are presented for the adsorption of CO on Ru(001), and for thermal annealing of a Ru(001) surface sputtered with argon ions at different energies.